Do CEO narcissism and board gender diversity influence the sustainable reporting of energy companies in Southeast Asia? - Sukmadilaga, Citra; Rizaldi, Danizar; Salmana, Saskia; Ghani, Erlane K (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze the factors that can influence sustainability reporting practices of energy companies in Southeast Asia. In particular, this study examines two factors, namely CEO narcissism and board gender diversity, which may influence sustainability reporting practices of energy companies in four countries: Indonesia, the Philippines, Thailand, and Malaysia. This study utilized content analysis of annual reports over a three-year period from 2017 to 2019 as the basis for data collection, resulting in 198 pieces of data over the entire period. The results of this study show that CEO narcissism and board gender diversity have a significant impact on the sustainability reporting of energy companies in the four Asian countries. Furthermore, the results of this study show that board gender diversity and CEO narcissism simultaneously have a significant impact on the sustainability reporting of energy companies. It is expected that this study will make a valuable contribution to the existing literature and serve as a reference point for future studies aimed at advancing knowledge and scholarship. The findings of this study not only provide a substantial contribution to the existing body of knowledge, but they also serve as a point of reference for further investigation into the field of sustainability reporting. This study can serve as a valuable reference for future research on the impact of corporate sustainability reporting in Southeast Asia.